MEDIA BOWLING CAREER UNTUK MENINGKATKAN PEMAHAMAN EKSPLORASI KARIR - Hartuti (Jurnal Riset Daerah, 2025)
Best practices in Group Guidance with bowling career media aim to improve students' career understanding. The method used is descriptive qualitative. Data obtained based on observations, implementation of group guidance with bowling career media and questionnaires. The subjects of this study were students in class XB of SMA Negeri 1 Bantul. Based on the best practices in group guidance with bowling career media, the following were carried out: Explaining material about careers to teenagers or generation Z, group discussions about careers in the digital era, student presentations on career selection, and group guidance with bowling career media. Based on the results of the questionnaire and group guidance with bowling career media, students were able to improve their understanding of the careers they would prepare for.